Soil Carbon Finance for MRV Hackathon Day 2: Insights from the first session - Costa, Ciniro (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Presentation slides from the second hackathon day in the Soil Carbon Finance for MRV Hackathon on 24 September 2020. This presentation was given by Ciniro Costa Jr., CCAFS, covering key messages and insights from the first session. Find out more: https://soilcarbon.weebly.com/